The Psychosocial Consequences of Sports Participation for Individuals with Severe Mental Illness: A Metasynthesis Review. (23rd February 2015) - Soundy, Andrew; Freeman, Paul; Stubbs, Brendon; Probst, Michel; Roskell, Carolyn; Vancampfort, Davy
Abstract : The purpose of the current metasynthesis review was to explore the psychosocial benefits of sport and psychosocial factors which impact on sports participation for individuals with severe mental illness. AMED, CINAHL Plus, Medline, EMBASE, ProQuest Nursing & Allied Health Source, and Science Citation Index were searched from inception until January 2014. Articles included use qualitative methods to examine the psychosocial effects of sports participation in people with severe mental illness. Methodological quality was assessed using the Consolidated Criteria for Reporting Qualitative Studies and a case study tool. Included studies were analysed within a metasynthesis approach. Eight articles involving 56 patients met the inclusion criteria. The results identified the broader and direct psychosocial benefits of sport. Sport provided a "normal" environment and interactions that were not associated with an individual's mental illness. Sport provided individuals with a sense of meaning, purpose, belonging, identity, and achievement. Other findings are discussed. Direct psychosocial benefits are a consequence of sports participation for the vast majority of individuals with severe mental illness. Further to this, sports participation was associated with a reduction in social isolation and an increase in social confidence, autonomy, and independence.